Incidence and perception of nursing students' academic incivility in Oman - Jansi Natarajan; Joshua Kanaabi Muliira; Jacoba van der Colff (BMC, 2017)
Abstract Background The incidence of incivility in nursing education is increasing in most countries and it is affecting the culture of safety and the teaching-learning processes. Despite reports of increasing trends, little is known about nursing students' academic incivility in the Middle East. This study aimed at exploring the perceptions and extent of academic incivility among nursing students (NS) and nursing faculty members (NF) in a university based undergraduate nursing program in Oman. Methods A quantitative cross sectional survey was used to explore NS academic incivility from the perspective of NS and NF in a public university in Oman. Data was obtained from a sample of 155 NS and 40 NF using the Incivility in Nursing Education Survey. Results There was agreement between NS and NF on the majority of behaviors perceived to be disruptive. The incidence of NS academic incivility was moderate. The most common uncivil behaviors were acting bored or apathetic in class, holding conversations that distract others in class, using cell phones during class, arriving late for class, and being unprepared for class. There were significant differences between NF and NS perceived incidence of uncivil behaviors such as sleeping in class (p = 0.016); not paying attention in class (p = 0.004); refusing to answer direct questions (p = 0.013); leaving class early (p = 0.000); cutting or not coming to class (p = 0.024); and creating tension by dominating class discussions (p = 0.002). Conclusion Student academic incivility is moderately present in nursing education in Oman, and this may have implications in terms of the future of the profession and patient care. There is need for more streamlined policies and strategies to curtail the incidence of academic incivility and to maintain safe and effective learning environments.